The terpene synthase gene family in Tripterygium wilfordii harbors a labdane‐type diterpene synthase among the monoterpene synthase TPS‐b subfamily. (14th February 2017) - Hansen, Nikolaj L.; Heskes, Allison M.; Hamberger, Britta; Olsen, Carl E.; Hallström, Björn M.; Andersen‐Ranberg, Johan; Hamberger, Björn
Summary: Tripterygium wilfordii (Celastraceae) is a medicinal plant with anti‐inflammatory and immunosuppressive properties. Identification of a vast array of unusual sesquiterpenoids, diterpenoids and triterpenoids in T. wilfordii has spurred investigations of their pharmacological properties. The tri‐epoxide lactone triptolide was the first of many diterpenoids identified, attracting interest due to the spectrum of bioactivities. To probe the genetic underpinning of diterpenoid diversity, an expansion of the class II diterpene synthase (diTPS) family was recently identified in a leaf transcriptome. Following detection of triptolide and simple diterpene scaffolds in the root, we sequenced and mined the root transcriptome. This allowed identification of the root‐specific complement of TPSs and an expansion in the class I diTPS family. Functional characterization of the class II diTPSs established their activities in the formation of four C‐20 diphosphate intermediates, precursors of both generalized and specialized metabolism and a novel scaffold for Celastraceae. Functional pairs of the class I and II enzymes resulted in formation of three scaffolds, accounting for some of the terpenoid diversity found in T. wilfordii . The absence of activity‐forming abietane‐type diterpenes encouraged further testing of TPSs outside the canonical class I diTPS family. Tw TPS27, close relative of mono‐TPSs, was found to couple with Tw TPS9, converting normal ‐copalyl diphosphate to miltiradiene. The phylogenetic distance to established diTPSs indicates neo‐functionalization of Tw TPS27 into a diTPS, a function not previously observed in the TPS‐b subfamily. This example of evolutionary convergence expands the functionality of TPSs in the TPS‐b family and may contribute miltiradiene to the diterpenoids of T. wilfordii . Significance Statement: Understanding how bioactive diterpenoids in the medicinal plant Tripterygium wilfordii are synthesized is a prerequisite to synthetic biology approaches for their biosynthesis. Here we mined a root transcriptome to search for diterpenoid biosynthetic enzymes. We found that expansions in families of diterpene synthases, , together with functional plasticity and neo‐functionalization, likely contributes to diterpene diversity in Tripterygium .